A comparative study on the heparin‐binding proteomes of Toxoplasma gondii and Plasmodium falciparum. Issue 15 (3rd July 2014) - Zhang, Yan; Jiang, Ning; Jia, Boyin; Chang, Zhiguang; Zhang, Yana; Wei, Xiaoyan; Zhou, Jianhua; Wang, Henan; Zhao, Xin; Yu, Shengchao; Song, Meng; Tu, Zhiwei; et al.
<x xml:space="preserve">Abstract</x> Toxoplasma gondii is an obligatory intracellular apicomplexan parasite which exploits host cell surface components in cell invasion and intracellular parasitization. Sulfated glycans such as heparin and heparan sulfate have been reported to inhibit cell invasion by T. gondii and other apicomplexan parasites such as Plasmodium falciparum. The aim of this study was to investigate the heparin‐binding proteome of T. gondii. The parasite‐derived components were affinity‐purified on the heparin moiety followed by MS fingerprinting of the proteins. The heparin‐binding proteins of T. gondii and P. falciparum were compared based on functionality and affinity to heparin. Among the proteins identified, the invasion‐related parasite ligands derived from tachyzoite/merozoite surface and the secretory organelles were prominent. However, the profiles of the proteins were different in terms of affinity to heparin. In T. gondii, the proteins with highest affinity to heparin were the intracellular components with functions of parasite development contrasted to that of P. falciparum, of which the rhoptry‐derived proteins were prominently identified. The profiling of the heparin‐binding proteins of the two apicomplexan parasites not only explained the mechanism of heparin‐mediated host cell invasion inhibition, but also, to a certain extent, revealed that the action of heparin on the parasite extended after endocytosis.